Finite element analysis of Arch concrete slab system for upper floors - Taslim, Kassim (2012)
Industrialized Building System (IBS) products are very prom1smg m Malaysia construction industry nowadays. Therefore, the Arch concrete slab system was innovatively designed to simplify the upper floors construction. This slab system has potential as an alternative method to design and build of the upper floors slabs in any multi storey buildings. The slab is constructed by using the precast concrete arch as permanent formwork and precast concrete beam made of lightweight concrete. The advantages of applying Arch concrete slab system are such as giving the extra strength to the structures, reduce the time of construction, environmental friendly, easy installation with minimum equipment and machineries needed, and unnecessary for using the scaffoldings during construction. This research is about the design and finite element analysis of precast arch concrete permanent formwork, precast concrete beam and Arch concrete slab system aided with an engineering software analysis such as ANSYS. The proposed model is designed so that it does not fail under deformation and shear stress. The results from the analysis shows that the proposed model of precast arch concrete as permanent formwork, precast concrete beam and Arch concrete slab system are safe and suitable for design and build for upper floors slabs in multi storey buildings.